2018
DOI: 10.1007/s13577-018-0217-y
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of lncTCF7 inhibits cell migration and invasion in colorectal cancer via inhibiting TCF7 expression

Abstract: The prognosis of colorectal cancer (CRC) is still very poor, owing to the high incidence of metastasis. Long noncoding RNA TCF7 (lncTCF7) has been shown to play critical roles in human CRC development and progression, but the molecular mechanisms of lncTCF7 in CRC are still unknown. This study aimed to explore the functions and molecular mechanisms of lncTCF7 on the migration and invasion of CRC cells. Notably, lncTCF7 was highly expressed in CRC cell lines relative to normal colonic epithelial cells. LncTCF7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…AC093818.1 is an antisense transcript of PDK1 17 , which is an oncogene known to promote tumorigenesis and metastasis 25,26 . Previous reports have indicated that antisense lncRNAs play important roles in tumorigenesis and metastasis [27][28][29][30][31] . However, the effects of natural antisense lncRNA AC093818.1 on tumorigenesis and metastasis remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…AC093818.1 is an antisense transcript of PDK1 17 , which is an oncogene known to promote tumorigenesis and metastasis 25,26 . Previous reports have indicated that antisense lncRNAs play important roles in tumorigenesis and metastasis [27][28][29][30][31] . However, the effects of natural antisense lncRNA AC093818.1 on tumorigenesis and metastasis remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Zhan et al [35] reported that TCF7 participates in the process of nasopharyngeal carcinoma as an oncogene. Consistently, Wu et al [36] demonstrated that TCF7 accelerates colorectal cancer cells to migrate and invade. In this paper, knockdown of APOC1 remarkably downregulated Wnt3a, β-catenin, CCND1 and TCF7 in RCC cells, whereas overexpression of APOC1 yielded the opposite trends.…”
Section: Discussionmentioning
confidence: 56%
“…For example, in hepatoma cells, transcription of the T-cell factor 7 (TCF7) gene is facilitated by lncRNA TCF7 via the recruitment of SWI/SNF complexes with the lncRNA TCF7 promoter (13). Likewise, recent research manifested that lncRNA TCF7 recruits BAF170 (SWI/SNF-related, matrix-associated, actin-dependent regulator of chromatin subfamily c member 2) to stimulate the TCF7 promoter and alter the expression of TCF7 in CRC (14). The data indicated that overexpression of lncRNA TCF7 can promote the occurrence of malignant behavior of CRC cells transfected with small interfering-lncRNA TCF7, thereby reversing the effect of lncRNA TCF7 on migration and invasion of CRC cells (14).…”
Section: Lncrnas and Dna Transcriptionmentioning
confidence: 99%
“…Likewise, recent research manifested that lncRNA TCF7 recruits BAF170 (SWI/SNF-related, matrix-associated, actin-dependent regulator of chromatin subfamily c member 2) to stimulate the TCF7 promoter and alter the expression of TCF7 in CRC (14). The data indicated that overexpression of lncRNA TCF7 can promote the occurrence of malignant behavior of CRC cells transfected with small interfering-lncRNA TCF7, thereby reversing the effect of lncRNA TCF7 on migration and invasion of CRC cells (14). The interplay between lncRNAs and DNA-binding proteins prevents these proteins from entering the DNA recognition element, thus inducing or inhibiting transcription dependent upon the nature of the target protein (15).…”
Section: Lncrnas and Dna Transcriptionmentioning
confidence: 99%